Writing Tudor exploration Richard Eden and West Africa - Dimmock, Matthew 1975- (Elements in travel writing, 2022)
"Richard Eden's Decades (1555) has long been recognised as a landmark in the translation and circulation of information concerning the Americas in England. What is often overlooked in Eden's book is the presence of the first two Tudor voyage accounts to have been committed to print, assembled in haste and added late in the printing process. Both concern English commercial ventures to the West African coast, undertaken despite vehement Portuguese protests and in the midst of the profound alteration of the Marian succession. Both are complex, contradictory, and innovative experiments in generic form and content. Writing Tudor Exploration closely examines Eden's assembly and framing of these accounts, engaging with issues of material culture, travel writing, new knowledge, race, and the negotiation of political and religious change. In the process it repositions West Africa and Eden at the heart of a lost history of early English expansionism"--